Executive Summary From the National Strength and Conditioning Association's Second Blue Ribbon Panel on Military Physical Readiness: Military Physical Performance Testing - Nindl, Bradley C; Alvar, Brent A; R Dudley, Jason; Favre, Mike W; Martin, Gerard J; Sharp, Marilyn A; Warr, Brad J; Stephenson, Mark D; Kraemer, William J (Journal of strength and conditioning research, 2015)
The National Strength and Conditioning Association's tactical strength and conditioning program sponsored the second Blue Ribbon Panel on military physical readiness: military physical performance testing, April 18-19, 2013, Norfolk, VA. This meeting brought together a total of 20 subject matter experts (SMEs) from the U.S. Air Force, Army, Marine Corps, Navy, and academia representing practitioners, operators, researchers, and policy advisors to discuss the current state of physical performance testing across the Armed Services. The SME panel initially rated 9 common military tasks (jumping over obstacles, moving with agility, carrying heavy loads, dragging heavy loads, running long distances, moving quickly over short distances, climbing over obstacles, lifting heavy objects, loading equipment) by the degree to which health-related fitness components (e.g., aerobic fitness, muscular strength, muscular endurance, flexibility, and body composition) and skill-related fitness components (e.g., muscular power, agility, balance, coordination, speed, and reaction time) were required to accomplish these tasks. A scale from 1 to 10 (10 being highest) was used. Muscular strength, power, and endurance received the highest rating scores. Panel consensus concluded that (a) selected fitness components (particularly for skill-related fitness components) are currently not being assessed by the military; (b) field-expedient options to measure both health-based and skill-based fitness components are currently available; and